PENDAMPINGAN ASUHAN KEBIDANAN DENGAN METODE ONE STUDENT ONE CLIENT (OSOC) TERHADAP AKSEPTOR KB MKJP DI KABUPATEN BANJARNEGARA - Dian Nirmala Sari; Reni Sumanti (Jurnal Ilmiah Medsains, 2020)
In order to reduce the rate of population growth, the government has implemented various development programs. MKJP is a government effort to suppress population growth. This study aims to determine the effect of midwifery care assistance with the One Student One Client (OSOC) method on the increase in KB MKJP acceptors in Banjarnegara. The research design used was quasy experimental, the design used was pre test post test control group design. In this study, divided into 2 groups, namely the control group and the treatment group. The number of samples used in this study amounted to 30 respondents. Univariate analysis was used to describe the data results from the pretest and posttest. Bivariate analysis using the Mc Nemar test using a significance level of 0.05 and 95% CI.The results showed a p value of 0.000, which means there is a significant change in the choice of contraceptives for respondents who are provided assistance with the OSOC method. Midwifery care assistance to pregnant women using the OSOC method for 3 months showed a difference in the choice of contraceptive methods in the intervention group and the control group.